2013
DOI: 10.1186/2193-1801-2-320
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and facilitators to self-care in chronic heart failure: a meta-synthesis of qualitative studies

Abstract: Chronic heart failure (CHF) is a costly condition that places large demands on self-care. Failure to adhere with self-care recommendations is common and associated with frequent hospitalization. Understanding the factors that enable or inhibit self-care is essential in developing effective health care interventions. This qualitative review was conducted to address the research question, "What are the barriers and facilitators to self-care among patients with CHF?” Electronic databases including Medline, EMBASE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
99
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(105 citation statements)
references
References 73 publications
(209 reference statements)
4
99
1
1
Order By: Relevance
“…As such, targeted intervention measures are required to improve their self-care abilities. [14]. Wang et al [15] found that education level was positively correlated with patients' abilities to self-manage medication, treatments, and administration of medication, and that higher education levels could facilitate compliance with adaptive healthy behaviours.…”
Section: Discussionmentioning
confidence: 99%
“…As such, targeted intervention measures are required to improve their self-care abilities. [14]. Wang et al [15] found that education level was positively correlated with patients' abilities to self-manage medication, treatments, and administration of medication, and that higher education levels could facilitate compliance with adaptive healthy behaviours.…”
Section: Discussionmentioning
confidence: 99%
“…Previously published reviews offer a more general account of self-care in HF or the experience of living with HF [38][39][40][41][42][43], rather than care seeking decisions specifically, or do not go beyond summarizing what is already reported in the literature [44].…”
Section: Figmentioning
confidence: 99%
“…A review of the literature indicated that existing studies on the education and training of patients with HF (4, 5, 13, 21) have addressed the importance of self-care behaviors (6,22), need for effective training interventions (7-9, 23) and effective training environments (14,24,25), application of theories of behavior change (17), and use of the HBM to educate HF patients (19,20,22). However, there are no comprehensive studies of the impacts of hospital-based educational programs based on the HBM on HF patients' self-care behaviors.…”
Section: Introductionmentioning
confidence: 99%